2020
DOI: 10.1139/apnm-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination and implementation of national physical activity, sedentary behaviour, and/or sleep guidelines among community-dwelling adults aged 18 years and older: a systematic scoping review and suggestions for future reporting and research

Abstract: Strategies for dissemination (purposive distribution of a guideline to specific audiences) and implementation (actions to support the general public in meeting guideline recommendations/behavioural benchmarks) of national movement guidelines (physical activity (PA), sedentary behaviour, and sleep) have yet to be synthesized. The purpose of this systematic scoping review was to identify strategies for dissemination and implementation of national PA, sedentary behaviour, and/or sleep guidelines among community-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 55 publications
2
25
0
1
Order By: Relevance
“…The systematic search retrieved 31 articles, of which the majority employed qualitative designs. Several negative responses were identified that, if addressed, may inform implementation strategies needed to ultimately improve uptake of guidelines [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systematic search retrieved 31 articles, of which the majority employed qualitative designs. Several negative responses were identified that, if addressed, may inform implementation strategies needed to ultimately improve uptake of guidelines [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise referral from general practitioners is common practice in several countries, including New Zealand and Canada; however, referral rates vary. In one UK study, general practitioners reported an overreliance on them to promote PA and advocated for a community of exercise medicine advocates, including other healthcare professionals (28,34).…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination and implementation challenges discussed here are not uncommon to national physical activity guidelines [ 49 52 ]. Across multiple countries, PA guidelines typically lack implementation strategies; dissemination strategies are more often included, but are not usually evaluated [ 50 , 52 ]. With the lack of strategic dissemination efforts, passive diffusion tends to occur, resulting in incomplete and inaccurate conveyance of national guidelines [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the lack of strategic dissemination efforts, passive diffusion tends to occur, resulting in incomplete and inaccurate conveyance of national guidelines [ 53 ]. The most effective dissemination and implementation strategies are unknown [ 49 , 50 ], and greater efforts are needed to identify, adapt, and test strategies to build the evidence on effective strategies in community (vs. clinical) settings (Harden SM, Balis LE, Houghtaling B, Powell B: Implementation strategies in community settings: an introduction to the Expert Recommendations for Implementing Change (ERIC) Compilation, submitted) and improve the overall public health impact of national physical activity guidelines.…”
Section: Discussionmentioning
confidence: 99%